Wear-resistant high-entropy alloy jointly reinforced by precipitated phase and gradient structure and preparation method of wear-resistant high-entropy alloy

By regulating the heat treatment process, the high-entropy alloy produces σ phase precipitation phase and gradient structure, which improves its wear resistance, solves the problem of insufficient wear resistance of existing high-entropy alloys, and achieves higher microhardness and average friction coefficient , simplifies the production process and is suitable for large-scale industrial production.

CN119243011APending Publication Date: 2025-01-03HUBEI UNIV FOR NATITIES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321560.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The performance of existing high-entropy alloys has not yet been optimized in terms of wear resistance, especially the average friction coefficient is between 0.45 and 0.63, which still needs to be further improved, and it is difficult for traditional processes to achieve large-scale industrial production.

Method used

By regulating the heat treatment process, the σ phase precipitation phase is generated inside the high-entropy alloy, and a gradient microstructure structure from coarse grains to fine grains is formed, forming high-level elements such as Fe, Co, Cr, Ni, Nb or V or Ti, etc. Entropy alloy, the micro Vickers hardness is 254.6~398.4HV, the average friction coefficient is 0.55~0.76, and the process is simple and controllable.

Benefits of technology

It significantly improves the wear resistance of high-entropy alloys, achieves a larger grain size span and microhardness, simplifies the production process, and facilitates large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243011A_ABST
    Figure CN119243011A_ABST
Patent Text Reader

Abstract

The invention relates to a wear-resistant high-entropy alloy jointly reinforced by a precipitated phase and a gradient structure, which comprises the following components in percentage by weight: 22-25% of Fe, 25-27% of Co, 24-26% of Cr, 21-23% of Ni and 1-3% of M, wherein the element M is one or more of Nb, V, Ti and Mo; the preparation method comprises the following steps: preparing raw materials; smelting in a vacuum furnace; performing homogenizing annealing; air cooling; hot rolling; water cooling; cold rolling to the product thickness; annealing is conducted; carrying out solution treatment; and water-cooling to room temperature for later use. By regulating and controlling the heat treatment process, a sigma-phase precipitated phase is generated in the high-entropy alloy, the grain size span is large, the average grain size of coarse grains is larger than or equal to 9.56 microns, the volume ratio of the coarse grains is 38-44%, the average grain size of fine grains is smaller than or equal to 3.21 microns, the volume ratio of the fine grains is 51-56%, the balance is the precipitated phase, the micro Vickers hardness of the high-entropy alloy is 254.6-398.4 HV, the average friction coefficient is 0.55-0.76, the production process is simple and convenient, and the production cost is low. The production process is simple and convenient, and large-scale industrial production is convenient to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high entropy alloy materials, and specifically refers to a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure and a preparation method thereof. Background Art

[0002] Metal surface wear refers to the inevitable energy loss phenomenon that the surface material of the friction pair is gradually lost as the friction behavior occurs, resulting in changes in the surface shape, size, position accuracy and surface properties of the parts. Surface wear of metal parts is the main cause of part failure. Wear is a common form of mechanical failure, accounting for about 80% of mechanical parts failure. Friction and wear not only increase the loss of raw materials and energy, but also cannot guarantee the safety and reliability of mechanical parts.

[0003] High entropy alloy is a complex alloy system without a principal element, which is composed of five or more elements in a certain molar ratio to ensure that the atomic fraction of each element is 5at% to 35at%. High entropy alloys are generally located in the central area of ​​the phase diagram, so their alloy composition space is very large and the formed organizational structure has many possibilities. In addition, high entropy alloys have high entropy effects in thermodynamics, slow diffusion effects in kinetics, lattice distortion effects in structure, and cocktail effects in performance, which are different from general alloys, so that high entropy alloys have some excellent mechanical properties, wear resistance, corrosion resistance, high temperature oxidation resistance and magnetic properties. Compared with traditional wear-resistant steels, the high mixing entropy and low high temperature diffusion rate of high entropy alloys make them more stable at high temperatures, and the lattice distortion hinders the movement of dislocations, resulting in a solid solution strengthening effect. The cocktail effect can give play to the particularity of different elements, and the synergistic effect is more obvious. The above characteristics make high entropy alloys have better working performance under extreme working conditions and have certain advantages in wear resistance.

[0004] The patent document with publication number CN117845118A discloses a multiphase high-entropy alloy with high strength, high toughness and wear resistance and its preparation method. By adjusting the Ti element content, the crystal structure of the alloy changes from FCC+BCC and Ni3Ti to BCC+Ni3Ti, thereby improving the strength and wear resistance. The average friction coefficient is between 0.45 and 0.63, which needs to be further improved.

[0005] The present invention regulates the heat treatment process to generate a σ phase precipitation phase inside the high entropy alloy and form a gradient microstructure in which coarse grains gradually transition to fine grains, thereby enhancing the wear resistance of the high entropy alloy. The method is controllable, reliable, easy to promote, and can be extended to other high entropy alloy materials of the same type. Summary of the invention

[0006] The object of the present invention is to provide a wear-resistant high entropy alloy which is strengthened by precipitation phase and gradient structure and has a large grain size span, wherein the average grain size of coarse grains is ≥9.56 μm, the volume ratio is 38-44%, the average grain size of fine grains is ≤3.21 μm, the volume ratio is 51-56%, and the rest is precipitation phase, the micro Vickers hardness is 254.6-398.4 HV, the average friction coefficient is 0.55-0.76, and the production process is simple, which is convenient for realizing large-scale industrial production of wear-resistant high entropy alloy strengthened by precipitation phase and gradient structure and preparation method.

[0007] Measures to achieve the above objectives:

[0008] A wear-resistant high-entropy alloy strengthened by precipitation phase and gradient structure, the components and weight percentage contents of which are: Fe: 22-25%, Co: 25-27%, Cr: 24-26%, Ni: 21-23%, M: 1-3%, wherein the M element is a composite addition of one or more of Nb, V, Ti or Mo; the microstructure of the high-entropy alloy is FCC phase and a small amount of σ phase; the structure of the high-entropy alloy is a gradient microstructure formed by coarse crystals and fine crystals, wherein the average grain size of the coarse crystals is ≥9.56μm, the volume ratio is 38-44%, the average grain size of the fine crystals is ≤3.21μm, the volume ratio is 51-56%, and the rest is precipitation phase.

[0009] A method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure, comprising the following steps:

[0010] 1) Raw materials configuration

[0011] Weigh Fe, Co, Cr, Ni, and M metal particles with purities all higher than 99.9% according to their respective value ranges;

[0012] 2) Melting in a vacuum furnace

[0013] The prepared raw materials are placed in a vacuum furnace for smelting. During this period, the vacuum cover is closed and the vacuum degree is kept at 2.5×10 -3 ~3.5×10 -3 Pa, introduce argon gas for stirring and melting; and control the whole process to repeat the melting 4 to 5 times; then cast into ingots, and the thickness of the ingots is controlled to be 40 to 45 mm;

[0014] 3) Perform homogenization annealing, control the annealing temperature at 1250-1300°C, and keep it at this temperature for 1-2 hours;

[0015] 4) Air cooling to 200-250°C;

[0016] 5) hot rolling, controlling the initial rolling temperature at 1050-1100°C and the final rolling temperature at 900-1000°C;

[0017] 6) Cooling by water cooling to 100-150°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature;

[0018] 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 85-90%;

[0019] 8) Annealing, controlling the annealing temperature at 600-800° C., and keeping the temperature at this temperature for 1-1800 seconds, and then water cooling again;

[0020] 9) Carry out solution treatment in a vacuum solution heat treatment furnace, control the solution temperature at 1000-1200°C, and keep it at this temperature for 1-1800s;

[0021] 10) Cool to room temperature and set aside.

[0022] Preferably, the homogenization annealing temperature is between 1255°C and 1285°C.

[0023] Preferably, the initial hot rolling temperature is between 1075 and 1090°C, and the final rolling temperature is between 915 and 985°C.

[0024] Preferably, the temperature is cooled to 110-145° C. at a water cooling rate of 24-30° C. / s.

[0025] Preferably, the annealing temperature is between 615°C and 780°C.

[0026] Preferably, the vacuum solution treatment temperature is between 1020 and 1180°C.

[0027] Functions and mechanisms of the components and main processes in the present invention

[0028] Fe: An appropriate amount of Fe element can improve the structural stability of the FCC phase, while improving the strength and hardness of the alloy. However, excessive Fe content will lead to a significant increase in oxide particles on the alloy surface. Excessive oxide particles will aggravate the abrasive wear phenomenon and significantly reduce the wear resistance. Therefore, the Fe content in the present invention is limited to 22-25%.

[0029] Co: The increase of Co element can usually increase the hardness of the alloy and reduce the wear rate, which is beneficial to the improvement of the wear resistance of the alloy. However, excessive Co may cause brittle phase or element segregation in the alloy, thereby reducing ductility. Therefore, the Co content is controlled in the range of 25-27%.

[0030] Cr: Cr is one of the common elements in high entropy alloys. It can promote the refinement of alloy grains. The increase in its content can usually improve the hardness and wear resistance of the alloy. However, when the Cr content is too high, it will lead to coarsening of the structure or adverse phase changes, thereby reducing the wear resistance. Therefore, the Cr content is controlled at 24-26%.

[0031] Ni: Ni element may promote the formation of FCC phase, and FCC phase usually has better plasticity and toughness, but its wear resistance is not as good as BCC phase or other hard phases; increasing Ni content can improve the yield strength and tensile strength of the alloy, but will reduce the hardness of the alloy, so the Ni content in the present invention is controlled at 21-23%.

[0032] Composite addition of one or more of Nb or V or Ti or Mo: Nb, V, Ti, and Mo elements are usually added to high-entropy alloys as high-melting-point metal elements. The refractory high-entropy alloys composed of such elements have high melting point characteristics and can effectively resist high-temperature wear caused by heating of the alloy friction pair. By regulating the type and content of the elements, the solid solution strengthening and the second phase precipitation can be enhanced to achieve a strengthening effect, thereby improving the toughness and wear resistance of the alloy. Therefore, in the present invention, the content is controlled to be no more than 3%.

[0033] The present invention closes the vacuum cover during vacuum smelting and waits until the vacuum degree reaches 2.5×10 -3 ~3.5×10 - 3 When the temperature is 0.04 Pa, argon is introduced for stirring and smelting to prevent the metal from reacting with oxygen at high temperature, thereby avoiding oxidation of the metal or the production of other unwanted compounds.

[0034] The reason why the present invention controls the homogenization annealing temperature at 1250-1300°C and keeps it at this temperature for 1-2 hours is to promote the diffusion of alloy elements, make the chemical composition inside the alloy more uniform, eliminate element segregation, and avoid melting of alloy grain boundaries and burning of main elements due to excessively high temperature or excessively long time, thereby reducing the performance of the alloy.

[0035] The reason why the initial rolling temperature is controlled at 1050-1100° C. and the final rolling temperature is controlled at 900-1000° C. is to refine the grains and improve the internal organizational structure.

[0036] The reason why the present invention cools to 100-150° C. at a cooling rate of 20-30° C. / s and then air cools to room temperature is to refine the grains and eliminate the internal stress generated in the alloy during the rolling process.

[0037] The reason why the cumulative deformation of cold rolling is controlled within 85-90% in the present invention is to further refine the grains and introduce a large number of dislocations and grain boundaries.

[0038] The reason why the present invention controls the annealing temperature at 600-1000° C. and keeps the temperature at 600-1000° C. for 1-1800 seconds is to promote the recrystallization of deformed grains in the alloy and promote the precipitation of the second phase.

[0039] The reason why the present invention controls the solid solution temperature at 1000-1200° C. and keeps the temperature at 1-1800 seconds is to obtain a suitable grain size and improve the strength and hardness of the alloy.

[0040] Compared with the prior art, the present invention regulates the heat treatment process to generate a σ phase precipitation phase inside the high entropy alloy, and the grain size span is large, wherein the average grain size of the coarse crystal is ≥9.56μm, the volume ratio is 38-44%, the average grain size of the fine crystal is ≤3.21μm, the volume ratio is 51-56%, and the rest is the precipitation phase, the micro Vickers hardness is 254.6-398.4HV, the average friction coefficient is 0.55-0.76, and the production process is simple, and the large-scale industrial production is easy to realize. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is the SEM organization diagram of the present invention. DETAILED DESCRIPTION

[0042] The present invention is described in detail below:

[0043] Table 1 is a list of chemical components of various embodiments and comparative examples of the present invention;

[0044] Table 2 is a list of main process parameters of various embodiments and comparative examples of the present invention;

[0045] Table 3 is a table of performance test results of various embodiments and comparative examples of the present invention.

[0046] Each embodiment of the present invention is produced according to the following steps

[0047] 1) Raw materials configuration

[0048] Weigh Fe, Co, Cr, Ni, and M metal particles with purities all higher than 99.9% according to their respective value ranges;

[0049] 2) Melting in a vacuum furnace

[0050] The prepared raw materials are placed in a vacuum furnace for smelting. During this period, the vacuum cover is closed and the vacuum degree is kept at 2.5×10 -3 ~3.5×10 -3 Pa, introduce argon gas for stirring and melting; and control the whole process to repeat the melting 4 to 5 times;

[0051] After casting into ingots, the thickness of the ingots is controlled at 40-45 mm;

[0052] 3) Perform homogenization annealing, control the annealing temperature at 1250-1300°C, and keep it at this temperature for 1-2 hours;

[0053] 4) Air cooling to 200-250°C;

[0054] 5) hot rolling, controlling the initial rolling temperature at 1050-1100°C and the final rolling temperature at 900-1000°C;

[0055] 6) Cooling by water cooling to 100-150°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature;

[0056] 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 85-90%;

[0057] 8) Annealing, controlling the annealing temperature at 600-800° C., and keeping the temperature at this temperature for 1-1800 seconds, and then water cooling again;

[0058] 9) Carry out solution treatment in a vacuum solution heat treatment furnace, control the solution temperature at 1000-1200°C, and at this temperature

[0059] Lower insulation 1~1800s;

[0060] 10) Cool to room temperature and set aside.

[0061] Table 1 Chemical composition list of various embodiments and comparative examples of the present invention (wt%)

[0062]

[0063] Table 2 List of main process parameters of various embodiments of the present invention and comparative examples

[0064]

[0065]

[0066] Table 2

[0067]

[0068] Table 3 List of mechanical properties test results of various embodiments of the present invention and comparative examples

[0069]

[0070]

[0071] From the results in Table 3, it can be seen that the high entropy alloy using the composition design and production process of the present invention has excellent wear resistance, its micro-Vickers hardness is 254.6-398.4HV, and the average friction coefficient is 0.55-0.76. Its wear resistance increases with the increase of the precipitation amount of the σ phase. The performance indicators of Comparative Example 1, which is not within the design range, are not as good as those of the embodiment, and the wear resistance is poor. Its micro-Vickers hardness is 132.4HV, and the average friction coefficient is 0.32. The average friction coefficient of the high entropy alloy of Comparative Example 2 is 0.82, and its wear resistance is higher than that of the high entropy alloy of the embodiment, but its elongation is only 18.3%, and the plasticity is poor, which does not meet the industrial needs.

[0072] This specific implementation is only the best example and is not a restrictive implementation of the technical solution of the present invention.

Claims

1. A wear-resistant high-entropy alloy strengthened by a precipitated phase and a gradient structure, wherein the components and weight percentage contents are: Fe: 22~25%, Co: 25~27%, Cr: 24~26%, Ni: 21~23%, M: 1~3%, wherein the M element is a composite addition of one or more of Nb or V or Ti or Mo; the microstructure of the high entropy alloy is FCC phase and a small amount of σ phase, and the structure of the high entropy alloy is a gradient microstructure formed by coarse grains and fine grains, wherein the coarse grain size is ≥9.56μm, the volume ratio is 38~44%, the fine grain size is ≤3.21μm, the volume ratio is 51~56%, and the rest is precipitation phase.

2. A method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure as claimed in claim 1, comprising the steps of: 1) Raw materials configuration Weigh Fe, Co, Cr, Ni, and M metal particles with purities all higher than 99.9% according to their respective value ranges; 2) Melting in a vacuum furnace The prepared raw materials are placed in a vacuum furnace for smelting. During this period, the vacuum cover is closed and the vacuum degree is kept at 2.5×10 -3 ~3.5×10 -3 Pa, introduce argon gas for stirring and melting; and control the whole process to repeat the melting 4 to 5 times; then cast into ingots, and the thickness of the ingots is controlled to be 40 to 45 mm; 3) Perform homogenization annealing, control the annealing temperature at 1250-1300°C, and keep it at this temperature for 1-2 hours; 4) Air cooling to 200-250°C; 5) hot rolling, controlling the initial rolling temperature at 1050-1100°C and the final rolling temperature at 900-1000°C; 6) Cooling by water cooling to 100-150°C at a cooling rate of 20-30°C / s, and then air cooling to room temperature; 7) Cold rolling to product thickness, controlling the rolling passes to 5-6 times, and the cumulative deformation to 85-90%; 8) Annealing, controlling the annealing temperature at 600-800° C., and keeping the temperature at this temperature for 1-1800 seconds, and then water cooling again; 9) Carry out solution treatment in a vacuum solution heat treatment furnace, control the solution temperature at 1000-1200°C, and keep it at this temperature for 1-1800s; 10) Cool to room temperature and set aside.

3. The method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure as claimed in claim 2, characterized in that: The homogenization annealing temperature is between 1255 and 1285°C.

4. The method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure as claimed in claim 2, characterized in that: The initial rolling temperature of hot rolling is 1075-1090°C, and the final rolling temperature is 915-985°C.

5. The method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure as claimed in claim 2, characterized in that: Cool to 110-145°C at a water cooling rate of 24-30°C / s.

6. The method for preparing a wear-resistant high entropy alloy gold strengthened by a precipitated phase and a gradient structure as claimed in claim 2, characterized in that: The annealing temperature is between 615 and 780°C.

7. The method for preparing a wear-resistant high entropy alloy strengthened by a precipitated phase and a gradient structure as claimed in claim 2, characterized in that: The vacuum solution treatment temperature is between 1020 and 1180°C.